Návrh marketingového plánu pro vybraný podnik - Luu, David (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Předmětem bakalářské práce je vytvoření návrhu marketingového plánu pro společnost Betonstropy s.r.o. a zavedení marketingových strategií do řízení společnosti. První část práce se zabývá teoretickými východisky, založenými na odborné literatuře. Druhá část je zaměřena na analýzu současného stavu podniku a jeho okolí. Poslední částí je vlastní návrh marketingového plánu.

The subject of this bachelor thesis is to create a marketing plan proposal for Betonstropy Ltd as well as a marketing-strategy implementation plan for the management of the company. The first part deals with theoretical bases based on specialized literature. The second part is the analysis of the curent state of company and its surroundings. The last part is the author’s own proposal of marketing plan.
Proposal of Marketing Plan for Selected Company
Keywords: Marketingový plán; marketing; marketingový mix; situační analýza; SWOT analýza; Marketing plan; marketing; marketing mix; situation analysis; SWOT analysis